A corner truncated fractal slot ultrawide spectrum sensing antenna for wireless cognitive radio sensor network. (22nd December 2020) - Goswami, Pankaj Kumar; Goswami, Garima
Summary: Due to the scarcity of the radio frequency spectrum, the emergent network sharing technique elicits the efficient use of licensed unutilized spectrum. Here, an ultra‐wideband (UWB) microstrip antenna is proposed for wireless cognitive radio sensor network (WCRSN). The antenna is uniquely designed for large spectrum scanning of channel vacancies in licensed frequency bands. Software‐defined radios (SDR) govern the algorithmic controls on spectrum sensing and channel interface using an appropriate antenna. The antenna comprises the effects of fractal slot patch and electromagnetic bandgap (EBG) ground structures on 12 × 18 × 1.6 mm 3 FR4 (relative dielectric constant of 4.4) substrate. Circular polarization is achieved through corner truncation to make antenna orientation free in wireless sensing networks. The measured |S11 | parameter offers 0.75‐ to 12‐GHz wide spectrum sensing with 2.51‐dBi average gain. The antenna is unique in compactness and includes lower edge bands of frequencies (0.75–3.1 GHz) along with UWB (3.1–12.0 GHz) for a very wide range scanning to utilize vacant channel opportunity in WCRSN through SDR. The proposed structure is experimented and validated for real‐time wideband scanning of the frequency spectrum within the operating limit as per the allotted FCC standard. Abstract : An ultra‐wideband (UWB) microstrip antenna is proposed for wireless cognitive radio sensor network (WCRSN). The antenna is uniquely designed for large spectrum scanning of channel vacancies in licensed frequency bands. The measured |S11 | parameter offers 0.75‐ to 12‐GHz wide spectrum sensing with 2.51‐dBi average gain. The antenna is unique in compactness and includes lower edge bands of frequencies (0.75–3.1 GHz) along with UWB (3.1–12.0 GHz) for a very wide range scanning to utilize vacant channel opportunity in WCRSN through SDR. The proposed structure is experimented and validated for real‐time wideband scanning of frequency spectrum within operating limit as per allotted FCC standard.